Maternal obesity disturbs the postnatal development of gonocytes in the rat without impairment of testis structure at prepubertal age - Christante, Caroline Maria [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Pinto-Fochi, Maria Etelvina [UNESP]; Goes, Rejane Maira [UNESP] (Bio Scientifica Ltd, 2013)
In this study, we evaluated whether maternal obesity (MO) affects testis development and gonocyte differentiation in the rat from 0.5 to 14.5 postnatal days. Male Wistar rats were used at 0.5, 4.5, 7.5, and 14.5 days post partum (dpp). These rats were born from obese mothers, previously fed with a high-fat diet (20% saturated fat), for 15 weeks, or normal mothers that had received a balanced murine diet (4% lipids). MO did not affect testis weight or histology at birth but changed the migratory behavior of gonocytes. The density of relocated cells was higher in MO pups at 0.5 dpp, decreased at 4.5 dpp, and differed from those of control pups, where density increased exponentially from 0.5 to 7.5 dpp. The numerical density of gonocytes within seminiferous cords did not vary in MO, in relation to control neonates, for any age considered, but the testis weight was 50% lower at 4.5 dpp. A wide variation in plasmatic testosterone and estrogen levels was observed among the groups during the first week of age and MO pups exhibited higher steroid concentrations at 4.5 dpp, in comparison with controls. At this age, higher estrogen levels of MO pups impaired the gonocyte proliferation. At 7.5 dpp, the testicular size and other parameters of gonocyte development are retrieved. In conclusion, MO and saturated lipid diets disturb gonocyte development and sexual steroid levels during the first days of life, with recovery at prepubertal age.